DEVELOPMENT OF A CLASSIFICATION OF TYPES OF INDIVIDUAL REACTIVITY AND THE ROLE OF INDIVIDUAL REACTIVITY IN PATHOGENIC PROCESSES - Иванов, Леонид Николаевич; Колотилова, Марина Леонидовна (Medicine in Kuzbass, 2021)
Substantiation of the existing literature there is no common view on the types of individual reactivity and the role of individual reactivity in the pathogenic process. A theoretical analysis of the material of domestic and foreign literature has been carried out. A classification of the types of individual reactivity of the organism has been developed and an interpretation of the role of each type of individual reactivity in the pathogenic process is presented. Recognition of this classification will allow unification of views on the types of individual reactivity and their role in the etiology, pathogenesis of the pathogenic reaction of the body, pathogenic process, pathogenic state and diseases, which is extremely important for theoretical and practical medicine. The classification of the types of individual reactivity developed by the authors includes normal and pathogenic individual reactivity. Pathogenic reactivity, like normal, includes: genetic immunogenic and non-immunogenic and acquired immunogenic and non-immunogenic reactivity.